Waste utilisation of urban trees for alternative furniture material - Hishammuddin, Ummu Aiman (2021)
Understanding the benefits provided by urban trees is important to justify the investment and to improve stewardship. Most of the end life of urban trees are either use as mulched or landfilled. As part of a commitment to sustainable urban trees, there is now a movement to use the entire tree. Thus, this research aims to identify the value of urban tree species and examine their waste that can be utilised as an alternative for furniture material. Seven major roads were selected in Kuala Lumpur, Malaysia as the areas for the case study. Methods such as literature review, tree inventory, observation and survey through questionnaire were performed to gather the significant data. The result acknowledged several valuable urban tree species whereas their waste can be transformed as furniture lumber. Towards the ends, prototype furniture has been made to show the value of material from the waste of urban trees based on selected tree species. The study also concluded with recommendations of good practice in managing the waste of urban trees for economic worth and sustainability for urban environments.